Improving Reading Comprehension Of The Students Of Economic Department At STIS Nuruddhalam Sumenep Through SQ3R Strategy - Shokhikhatul Khasanah (Institut Kariman Wirayudha Sumenep, 2019)
This research was conducted to improve the reading comprehension ability of the students of Economic Department at STIS Nuruddhalam, Sumenep through SQ3R strategy. Due to the problem found that the reading comprehension ability of the students to comprehend the text was unsatisfactory. This research employed two –cycle’s classroom action research and implemented in the 20 students of the first semester of the Students of Economic Department STIS Nuruddhalam, Sumenep. The instruments to collect the data were observation sheet, field notes and the reading comprehension test. The result of this research dicated that SQ3R strategy improved the student's reading comprehension ability that can be seen from the student's score in post test through their gain compare with their score in pretest. In cycle I there were 10 out of the students (50%) achieved 10 points greater than their score in pretest. While in cycle II, there were 15 students out of 20 students (75%) achieved 10 points greater than their score in pretest. Besides, the implementation of the SQ3R strategy was successful in improving the students' participation.